Constitutional Law: Study guide - Bakumov, O. S.; Бакумов, О. С.; Varunts, L. D.; Варунц, Л. Д.; Gudz, T. I.; Гудзь, Т. І.; Kolomiets, Yu. M.; Коломієць, Ю. М.; Lohvynenko, Ye. S.; Логвиненко, Є. С.; Marchuk, M. I.; Марчук, М. І.; et al. (Kharkiv National University of Internal Affairs, 2023)
The Study guide examines the main issues of the constitutional law theory, reveals its subject, system and sources. Based on the analysis of national legal systems, the content of different countries cons-titutions and modern achievements of legal science, the main provisions of the world countries constitutional law, including Ukraine, are highlighted. The institutions of Ukrainian constitutional law are analyzed as well as their inherent features, the specifics of the social relations regulation by the constitutional law norms, the legal status of the constitutional-legal relations subjects, their law-appli-cation activities, and the peculiarities of constitutional-legal responsibility are established. For practical employees of the National Police of Ukraine, scientists, adjuncts, graduate students, cadets, trainees and students of the Ministry of Internal Affairs of Ukraine and other legal educational institutions.

У навчальному посібнику розглядаються основні питання теорії конституційного права, розкриваються її предмет, система та джерела. На основі аналізу національних правових систем, змісту конституцій різних країн та сучасних досягнень правової науки висвітлено основні положення конституційного права країн світу, в тому числі України. Проаналізовано інститути конституційного права України, притаманні їм ознаки, специфіку регулювання суспільних відносин нормами конституційного права, правовий статус суб’єктів конституційно-правових відносин, їх правозастосовну діяльність, особливості конституційно-правової відповідальності. Для практичних працівників Національної поліції України, науковців, ад'юнктів, аспірантів, курсантів, слухачів і студентів МВС України та інших юридичних навчальних закладів.

В учебном пособии рассматриваются основные вопросы теории конституционного права, раскрываются ее предмет, система и источники. На основе анализа национальных правовых систем, содержания конституций разных стран и современных достижений юридической науки освещаются основные положения конституционного права стран мира, в том числе Украины. Анализируются институты конституционного права Украины, устанавливаются их присущие им признаки, специфика регулирования общественных отношений нормами конституционного права, правовой статус субъектов конституционно-правовых отношений, их правоприменительная деятельность, особенности конституционно-правовой ответственности. Для практических работников Национальной полиции Украины, ученых, адъюнктов, аспирантов, курсантов, слушателей и слушателей МВД Украины и других юридических учебных заведений.
Конституційне право: навчальний посібник
Keywords: Україна; Навчальні видання. Educational edition. Учебные издания; конституційне право; Ukraine; constitutional law; Украина; конституционное право; constitutional law as a branch of law; constitutional law as a science; constitutional law as an academic discipline; конституційне право як галузь права; конституційне право як наука; конституційне право як навчальна дисципліна; Constitution as the fundamental law of society and the state; Конституція як основний закон суспільства і держави; constitutional system; конституційний лад; конституційно-правовий статус особи; constitutional and legal status of a person; gender equality; гендерна рівність; гендер; forms of direct democracy; форми прямої демократії; system of public authorities; система органів державної влади; head of state; глава держави; parliament; парламент; government; уряд; judiciary; судова влада; constitutional control; конституційний контроль; police; поліція; ensuring constitutional rights and freedoms of a person and citizen; забезпечення конституційних прав і свобод людини і громадянина; territorial organisation of public authorities; територіальна організація органів державної влади